2004
DOI: 10.1161/01.atv.0000148006.78179.c7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of High Concentration of Glucose on Relaxations to Activation of ATP-Sensitive K + Channels in Human Omental Artery

Abstract: Objective-The present study was designed to examine in the human omental artery whether high concentrations of D-glucose inhibit the activity of ATP-sensitive K ϩ channels in the vascular smooth muscle and whether this inhibitory effect is mediated by the production of superoxide. Methods and Results-Human omental arteries without endothelium were suspended for isometric force recording.Changes in membrane potentials were recorded and production of superoxide was evaluated. Glibenclamide abolished vasorelaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 50 publications
(20 reference statements)
0
35
0
Order By: Relevance
“…In humans as well as animals, diabetes mellitus impairs the activity of ATP-sensitive K ϩ channels in vascular smooth muscle cells, resulting in decreased vasodilation mediated by these channels (Mayhan and Faraci, 1993;Zimmermann et al, 1997;Miura et al, 2003). Our recent study has demonstrated that in the human artery, high concentrations of glucose reduce the activity of ATP-sensitive K ϩ channels (Kinoshita et al, 2004). These studies indicate that hyperglycemia as well as diabetes mellitus affects vasodilation mediated by ATP-sensitive K ϩ channels in human blood vessels.…”
Section: Atp-sensitive Kmentioning
confidence: 72%
See 1 more Smart Citation
“…In humans as well as animals, diabetes mellitus impairs the activity of ATP-sensitive K ϩ channels in vascular smooth muscle cells, resulting in decreased vasodilation mediated by these channels (Mayhan and Faraci, 1993;Zimmermann et al, 1997;Miura et al, 2003). Our recent study has demonstrated that in the human artery, high concentrations of glucose reduce the activity of ATP-sensitive K ϩ channels (Kinoshita et al, 2004). These studies indicate that hyperglycemia as well as diabetes mellitus affects vasodilation mediated by ATP-sensitive K ϩ channels in human blood vessels.…”
Section: Atp-sensitive Kmentioning
confidence: 72%
“…These studies indicate that hyperglycemia as well as diabetes mellitus affects vasodilation mediated by ATP-sensitive K ϩ channels in human blood vessels. In addition, these pathophysiological conditions appear to produce increased levels of superoxide in the vasculature, leading to inhibition of ATP-sensitive K ϩ channel activity (Liu and Gutterman, 2002;Kinoshita et al, 2004). Therefore, it is crucial to explore tools by which one can reduce oxidative stress in blood vessels to ameliorate the impaired vascular function produced by glucose intolerance.…”
Section: Atp-sensitive Kmentioning
confidence: 99%
“…85,86 In addition, ROS directly depolarize vascular smooth muscle cells by inhibiting various potassium channels. [87][88][89] The Intercellular Links: Gap Junctions Endothelium-dependent contractions to acetylcholine are smaller in layered bioassay ("sandwich") preparations than in intact rings, 77 illustrating that the contact between endothelial and vascular smooth muscle cells is important in the genesis of EDCF-mediated responses. In bioassay preparations, the endothelium-derived prostanoids diffuse freely across the intercellular gap between the donor (containing endothelial cells) and the effector (without endothelium, responsible for the contraction), and cell-impermeable antioxidants reduce the response to acetylcholine, whereas they do not in intact rings in which intracellular antioxidants inhibit EDCFmediated responses.…”
Section: The Mediators: Prostanoidsmentioning
confidence: 99%
“…85,86 In addition, ROS directly depolarize vascular smooth muscle cells by inhibiting various potassium channels. [87][88][89] …”
Section: The Mediators: Prostanoidsmentioning
confidence: 99%
“…In addition, accumulating evidence has revealed that DM has been associated with dysfunction of the cardiovascular K ATP channels (Weintraub 2003). Hyperglycemia and DM impair vasodilation mediated by K ATP channels in human vascular smooth muscle cells (Miura et al 2003, Kinoshita et al 2004, Kinoshita et al 2006. Furthermore, a recent study shows that diabetes reduces mitoK ATP expression and function.…”
Section: Introductionmentioning
confidence: 99%